Polymorphisms in myeloperoxidase and tissue inhibitor of metalloproteinase-1 genes and their association with preeclampsia in the Chinese Han population - Li Liu; Dong He; Weilin Zhou; Zhiyang Guo; Yue Ma; Lingjie Liu; Hong He; Shuqi He; Yi Huang (Heliyon, 2024)
Hypertensive disorders of pregnancy (HDP) are multifaceted syndromes unique to pregnancy, characterized by increased blood pressure, edema, and proteinuria. Patients with HDP exhibit signs of endothelial dysfunction, possibly linked to increased myeloperoxidase (MPO) level and aberrant oxidative stress. Additionally, altered level of tissue inhibitor of metalloproteinase-1 (TIMP1) protein is associated with placental ischemia, hypoxia, and maternal vascular endothelial damage. Preeclampsia (PE) represents a critical stage of HDP that poses severe threats to maternal and fetal safety. This study aimed to determine the relationship between MPO and TIMP1 polymorphisms and the risk of PE in the Chinese Han population. Single nucleotide polymorphisms (SNPs), including MPO rs7208693, MPO rs2243828, and TIMP1 rs6609533, were genotyped in 170 patients with PE and 303 control participants. No significant association was observed between MPO polymorphisms (rs7208693 and rs2243828) and the risk of PE, whereas significant association between the TIMP1 rs6609533 A > G SNP and PE susceptibility was found. Specifically, individuals with the GG or AG genotypes had elevated risk of PE compared to those harboring the AA genotype. Furthermore, in the PE group, patients carrying the G allele were more likely to experience fetal growth restriction (FGR). In the non-PE group, the association between the G allele and the risk of FGR was not evident. In conclusion, the TIMP1 rs6609533 G allele in Chinese Han women was identified as a risk factor for PE. Our results indicated that the TIMP1 rs6609533 SNP can serve as a biomarker for the clinical diagnosis and treatment of PE.